LIMBAH GERGAJI KAYU SEBAGAI BAHAN FORMULA MEDIA JAMUR SHIITAKE (LENTINULA EDODES) - Netty Widyastuti (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The sawdust can be utilized as mushroom formulation medium , like shiitake (Lentinus edodes /Lentinula edodes). The antitumor properties of lentinus are attributed to the presence of polysaccharide lentinan. Lentinan can be utilized as reducing diabetes, and effective to againts influenza virus. Usually, Albazia falcataria sawdust were utilized by mushroom growers in Indonesia. Optimum temperature for shiitake growth is 24oC and pH4.7 – 4.8 (mycelium phase), 20oC and pH 4.2 – 4.6.(fruit body phase). The elevation for best cultivation is 800 – 1000 m above sea level, humudity almost 95 – 100%. Ifused log system, shiitake will be harvested after 2-3 months fruiting bodies were produced. Biological efficiency (BER) was 45%.